The Relationship Between Age and Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus Outpatient at Wonogiri Health Center, North Lampung in 2024 - Wardhani, Erma Septya; Junita, Dera Elva; Wati, Desti Ambar; Khairani, Masayu Dian (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The purpose of this study was to determine the relationship between nutritional status, carbohydrate intake, and fiber intake on blood sugar levels of type 2 diabetes mellitus patients at Wonogiri Health Center. Method: This study was conducted in December 2024. This research design uses analytic observational quantitative research with a cross sectional approach. The sample of this study were patients diagnosed with type 2 diabetes mellitus in the Wonogiri Health Center work area as many as 57 respondents. Bivariate analysis of this study using the Spearman Rho test. Result: his study shows that there is no significant relationship between age and blood sugar levels of respondents (Sig. > 0.05). This happens because each individual has differences regarding other risk factors such as lifestyle, physical activity that may affect the condition of type 2 diabetes mellitus patients. Conclusion: There is a significant relationship between age and blood sugar levels of respondents.